Embryonal Rhabdomyosarcoma of Prostate in Adult: A Rare Case Report - Andhika, Dimas Panca; Hardjowijoto, Sunaryo (Folia Medica Indonesiana, 2021)
Rhabdomyosarcoma is the fifth most common type of soft tissue solid tumor in children and the most common in the last two decades. Rhabdomyosarcoma of the urogenital organ is a rare mesenchymal tumor, covering 22% of all Rhabdomyosarcoma cases. The two most common histologic types are alveolar and embryonal, whereas botryoid and spindle cells are rarely found. We reported a case of embryonal Rhabdomyosarcoma of the prostate. In this study, we improved the understanding of Embryonal Rhabdomyosarcoma of the prostate on 23 years old male who had a history of swelling in the perineal area and a history of falling from a height in the groin area 5 months before. The patient complains of the difficulty of urinating and hematuria one month after falling. We underwent drainage of the swelling area, found pus 100cc and took a sample for pathological examination. The result was embryonal rhabdomyosarcoma. Prostate volume was 122cc, PSA 5,32 and PSAD 0,04. The CT scan result was solid mass size 15x8x18 cm at perineum enhance to the pelvic cavity, push the bladder to the superior, rectum to posterior, and urethra posterior to the left side. We diagnosed this patient as Embryonal Rhabdomyosarcoma prostate T2bG1N0M0 (stage 3) group 3 and intermediate-risk group. The patient underwent VAC chemotherapy based on D.9803 (IRS V) protocol and planned radiotherapy, but it stopped at halfway because of profuse bleeding. Embryonal Rhabdomyosarcoma is an aggressive tumor, especially in adults. However, there was limited evidence and guideline to diagnose and manage the disease.